Postural control physiology specifics in elite hurdle racers due to long-term motor specialization - Semchenko, A. A.; Nenasheva, A. V.; Izarovskaya, I. V.; Zadorina, E. V.; Baymukhametova, E. F. (Theory and Practice of Physical Culture, 2018)
The study applied a computerized stabilometry system to analyze the postural control physiology specifics in elite hurdle racers (n=12) and found variations in the static/ kinetic stability rates indicative of the cross motor stereotypes being formed under specific training and competitive loads, with the counter-lateral synchronization of the relevant proprioceptors and myotatic reflexes. The study data and analysis of the stabilogram and statokinesiograms may be highly beneficial for the hurdle racers` training and competitive process correction. At the special skills excelling stage when the slow high-amplitude oscillating movements are trained, it is recommended to apply special stands with or without balancing weights to improve the static component of the static/ kinetic balancing skills. The study data showed the precompetitive redistribution of the performance oscillations in the elite hurdle racers` stabilograms with domination of the medium-frequency amplitudes in the frontal and sagittal planes that may be indicative of the high balance in the specific kinematic chain (movement sequence). The stabilometry tests of the hurdle racers with the sensor-vestibular tests in the training and competitive processes showed low variations in the key static/ kinetic balance rates including dynamic balance ratio, stability index and stability rate.